Structural Characterization and Anti-complementary Activities of Two Polysaccharides from Houttuynia cordata - Lu, Yan; Zhang, Juan-Juan; Huo, Jiang-Yan; Chen, Dao-Feng (Planta Medica, 2019)
In previous studies, crude Houttuynia cordata polysaccharides showed beneficial effects on acute lung injury in vivo, a syndrome in which anti-complementary activities played an important role. Anti-complementary activity-guided fractionation of H. cordata polysaccharides led to the isolation of two highly branched homogeneous polysaccharides, HC-PS1 and HC-PS3, with a molecular weight of 274 530 and 216 384 Da, respectively. The polysaccharides were purified by chromatography on DEAE-cellulose and Superdex columns. Their structural characterization was performed by IR, GC-MS, methylation, NMR, and SEM analysis. Both HC-PS1 and HC-PS3 are composed of eight types of monosaccharides, including rhamnose, arabinose, mannose, glucose, glucuronic acid, galactose, galacturonic acid, and xylose. The main linkages of the sugar residues in HC-PS1 include terminal Rhap, terminal and 1,5-linked Araf; 1,3,6-linked and 1,4,6-linked Manp; terminal, 1,4-linked, 1,3-linked, 1,3,6-linked and 1,4,6-linked and 1,3,4,6-linked Glcp; and terminal, 1,4-linked and 1,6-linked Galp. The main monosaccharide linkages in HC-PS3 are similar to that of HC-PS1, except the additional 1,3,4-linked Manp and the absence of 1,3,6-linked Glcp. HC-PS1 and HC-PS3 were found to inhibit complement activation through both the classical and alternative pathways with 50% inhibition concentrations of 0.272 – 0.318 mg/mL without interfering with the coagulation system. Preliminary mechanism studies indicated that both HC-PS1 and HC-PS3 inhibited the activation of the complement system by interacting with C2, C4, and C5. The results suggest that HC-PS1 and HC-PS3 could be valuable for the treatment of diseases associated with the excessive activation of the complement system.
Keywords: Houttuynia cordata; Saururaceae; homogeneous polysaccharide; structural characterization; anti-complementary activity